2020
DOI: 10.1080/01605682.2020.1824553
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and comparative analysis of the multi-level parsimonious AHP methodology in a public transport development decision problem

Abstract: The methodology of Parsimonious Analytic Hierarchy Process (PAHP) has been originally constructed to unburden the evaluators of an AHP survey from the numerous pairwise comparisons caused by the several alternatives in decision problems. So far, there are very few applications of PAHP and all of them referred to the last level of the decision structure; to the alternatives. This paper aims to demonstrate a multi-level PAHP based model, so how to apply the method on an arbitrary level of the decision structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Then, using the relative weights (local priorities) calculated for the reference points and the initial weights assigned to the remaining alternatives, an interpolation procedure is applied to derive the relative weights (local priorities) of the latter alternatives. Duleba (2020) extends the same intuition to a multi-level structure. To better compare the enhanced versions of AHP, we implement these methods using a numerical example analyzed many times in the AHP literature.…”
Section: Comparing the Judgments Required Across Methodsmentioning
confidence: 70%
“…Then, using the relative weights (local priorities) calculated for the reference points and the initial weights assigned to the remaining alternatives, an interpolation procedure is applied to derive the relative weights (local priorities) of the latter alternatives. Duleba (2020) extends the same intuition to a multi-level structure. To better compare the enhanced versions of AHP, we implement these methods using a numerical example analyzed many times in the AHP literature.…”
Section: Comparing the Judgments Required Across Methodsmentioning
confidence: 70%
“…Table 5 shows the gained normalized increasing order: Still in this step, we had to select some reference criteria to be compared in the later stage of multi-level Parsimonious AHP methodology. As selection criteria, the PAHP literature [39,44] recommends keeping the s number of selected attributes low enough for easier pair wise comparisons and, simultaneously, high enough to represent the set of the elements of the Parsimonious level. In this case study, three reference attributes (the most and the least important and an intermediate based on the first direct evaluations) seemed sufficient to select.…”
Section: Results Of the Parsimonious Ahp Surveymentioning
confidence: 99%
“…The second tool particularity used in our application is the new Parsimonious AHP (PAHP). This novel technique was recently introduced by Abastante et al ( 2019 ) and there are still very few applications reported (Abastante et al, 2018 ; Duleba, 2020 ). We believe that this technique will become prominent in the future and the present study contributes to its consolidation by testing it in the current framework.…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…One of them is the fact that the AHP tool not only enables to simultaneously capture subjective and objectives aspects of the decision-maker’s choice in a quantifiable manner but also permits the participation of non-experts, such as children, by invoking simple pairwise comparisons. In addition, AHP features cyclicality, which enables to evaluate the consistency of assessments made by the decision makers by checking procedure and rank reversal in case of inconsistencies (Duleba, 2020 ).…”
Section: Relevant Literaturementioning
confidence: 99%